SPECIES COMPOSITION, LATITUDINAL AND ALTITUDINAL DISTRIBUTION OF CADDISFLIES IN HILL STREAMS OF SOUTHERN EASTERN GHATS - R. Y. REKHA; S. DINAKARAN (The Bioscan, 2013)
A total of 789 individuals of aquatic insects were collected from six selected streams of Southern Eastern Ghats. The objective of the present study is to address the latitudinal and altitudinal distribution of larval Caddisflies in the different streams of Southern Eastern Ghats. High family and generic richness was recorded in 11º47’80" N which is considered as highest degree of latitude among the visited sites located in Yercaud hills which corresponds to the altitude of 1161m. The Altitudinal and Latitudinal gradient offers excellent opportunities to investigate factors which control the diversity, composition and abundance of Caddisflies in streams of Southern Eastern Ghats. The present study clearly reveals that maximum diversity is confined to higher altitudes among sampled locations. Due to reduction in rainfall and global warming the stream flow is restricted to higher elevations and harbors maximum diversity.